(untitled) - Hooyman, Nancy R; Gonyea, Judith (Thousand Oaks, 1995)
"Published in cooperation with the Center for Practice Innovations, Mandel School of Applied Social Sciences, Case Western Reserve University"; Includes bibliographical references (p. 357-393) and indexes; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Caregivers -- Government policy -- United States; Family policy -- United States; Feminist theory -- United States; Home care services -- Social aspects -- United States; People with disabilities -- Home care -- United States; Sex role -- United States; Người chăm sóc -- Chính sách của chính phủ -- Hoa Kỳ; Chính sách gia đình -- Hoa Kỳ; Lý thuyết nữ quyền -- Hoa Kỳ; Dịch vụ chăm sóc tại nhà -- Khía cạnh xã hội -- Hoa Kỳ